The effectiveness of locally produced protein bait improved with papain in capturing fruit flies of mango - Umeh, V.C.; Olaniyi, M.A.; Manga, J. (Fruits, 2021)
Introduction – Fruit flies adversely affect the fruit industry in Nigeria, especially small holders who cannot afford the cost of imported insect control inputs. Consequently, local alternatives are being developed to benefit these farmers. Materials and methods – Locally made protein bait from autolysed brewery yeast waste (BYW) to which different concentrations of crude papain were separately added in traps was tested. The treatments included: X1 = 188.5 mL BYW + 11.5 mL crude papain mixed in 1,300 mL of water; X2 = 191 mL BYW + 9.0 mL crude papain in 1,300 mL of water; X3 = 200 mL BYW in 1,300 mL of water. One pellet of Torula yeast in 200 mL of water (T0) served as the check. A 7-ha orchard planted to ‘Tommy Atkin’ mango variety was partitioned into three blocks (replicates). The four different baits at 300 mL trap-1 were allotted randomly to mango trees 50 m apart in each block. The baits were replaced every 7 days after removal of trapped insects. Results and discussion – Weekly observations showed that captured fruit flies ranged from mean of 1.7–7.6 flies trap-1 day-1 out of which 95% were females. The species collected included Bactrocera dorsalis, Ceratitis cosyra, C. silvestri and C. dittissima with a dominance of B. dorsalis (over 90%). There was no significant (p>0.05) difference between the number of fruit flies attracted by T0 compared to X1 at the end of the trial. However, the number captured by T0 and X1 were significantly (P<0.05) higher than X2 and X3. Conclusion – The result showed that BYW enhanced with crude papain can be as effective as Torula® in attracting different fruit fly species.